Macular Ganglion Cell-Inner Plexiform Layer, Ganglion Cell Complex, and Outer Retinal Layer Thicknesses in a Large Cohort of Chinese Children - Cheng, Lu; Wang, Mingjin; Deng, Junjie; Lv, Minzhi; Jiang, Wenhan; Xiong, Shuyu; Sun, Sifei; Zhu, Jianfeng; Zou, Haidong; He, Xiangui; Xu, Xun (Investigative ophthalmology & visual science, 2019)
The purpose of this study was to describe the normative values, distribution patterns, and correlated factors of macular ganglion cell-inner plexiform layer (GCIPL), ganglion cell complex (GCC), and outer retinal layer (ORL) thicknesses in Chinese children. A sample of 3000 healthy children with different refractive status aged 6 to 19 years was consecutively examined. Demographics were recorded, and a comprehensive ophthalmic examination including refractive error and axial length (AL) was taken from all participants. The GCIPL, GCC, and ORL thicknesses were measured using swept source-optical coherence tomography (OCT), and multiple linear regression was used to determine which factors were associated with the thickness of each layer. The average thickness was 77.00 ± 4.78 μm (95% confidence interval [CI]: 69.56-84.56 μm) in the GCIPL, 107.68 ± 5.95 μm (95% CI: 98.45-117.21 μm) in the GCC, and 178.57 ± 9.02 μm (95% CI: 164.33-192.56 μm) in the ORL. Multiple regression analysis indicated that GCIPL thickness was associated with sex (β = 0.168, P < 0.001), age (β = 0.126, P < 0.001), axial length (β = -0.181, P < 0.001), and refractive error (β = 0.233, P < 0.001). Age (β = 0.154, P < 0.001), sex (β = 0.102, P < 0.001), and refractive error (β = 0.149, P < 0.001) were associated independently with GCC thickness after adjusting for the other factors. Furthermore, age (β = 0.100, P < 0.001), sex (β = 0.163, P < 0.001), AL (β = -0.283, P < 0.001), and refractive error (β = 0.207, P < 0.001) were the independent factors associated with ORL thickness. The present study established a normative pediatric database for macular layer thicknesses in healthy Chinese children, advancing the ability of OCT in diseases diagnosis and monitoring among children.